National Minority Education in Croatia - Mesić, Milan (2004)
The paper presents first the ethnic structure of Croatia and juridical protection( including rights to minority education) of its legally recognized national minorities. Then, the central part is dedicated to the discussion on the models of schooling of national minorities in Croatia. At the end, several ideas are suggested for promotion of national minorities and their better integration in a multicultural society.